El fortalecimiento del desarrollo integral del niño a través de actividades lúdicas - Dueñas Amaya, Estefanía Alexandra (2016)
Early Childhood Education Career contributes to the children integral development at early ages, sensing to improve the kindergarten children academic level, with using proper leisure activities, so contributing to the teaching and learning progress, due to ignorance of this activity is considered the application of this educational methodology for children intellectual progress. This research is based on the cognitivist theory; this is a process that leads to the naturall and real knowledge in order contribute to the society entity. By Piaget and Montessori it is focused on two important authors, who introduced themselves and talked about the games into de children. The impact of this study is to determine whether the recreational activities contributed to the intellectual development, motor, language and emotional being these areas of development children, improving their relationship with the social and natural environment, which will be reflected in actions to undertake sharing a pleasant and enjoyable time with their peers in the future. An Interactive Guide development was based on this reseach which has a series of dynamic activities for children teaching-learning process, creating a comprehensive development in them, forged this significant knowledge so in a way it was proposed fun, dynamic and innovative without the need of using technological means considering that they must be an active entity in daily living. The project aims that teachers and parents take the game as a factor enabling them to improve motor activity, social interaction, and cognitive development and at the same time determine the different skills and abilities that are forged in them. The deductive, inductive, qualitative and quantitative method were used and also in this methodology process 100 children from "Hermano Miguel" Educational Unit Initial Level 2, were benefited.